Vendor Seleection in E-Commerce Using the Analytical Hierarchy Process Method - Yosiyanto, Robi; Handayani, Sri; Rahardjo, Sri; Ricardianto, Prasadja; Indrawan, Rully; Fachrial, Peppy (Institut Transportasi dan Logistik Trisakti, 2024)
The development of the e-commerce business is an opportunity for logistics service providers as third parties who deliver goods sold by the seller to the location intended by the buyer. This study aims to analyze the behavior of fashion e-commerce customers in choosing the best vendor. Data were collected by in-depth interviews with five selected informants for vendor criteria and sub-criteria, then a survey was conducted on 100 respondents. The data were analyzed using the Analytical Hierarchy Process method to determine criteria and sub-criteria in selecting the preferred vendor. The first criterion was reliability of delivery, with the sub-criteria of timeliness, accuracy of delivery destination, and security of the condition of the goods. The second criterion was price. The next criterion was products with regular delivery, express, and same-day sub-criteria. The last criterion was shipping features with its sub-criteria shipping tracking, wide delivery area, and customer service. For the case of Indonesia in this study, the best vendor in delivering products from e-commerce to customers is obtained by Si Cepat in the first place, followed by J&T and JNE in second and third places.